Bioactive components in Bambara groundnut (Vigna subterraenea (L.) Verdc) as a potential source of nutraceutical ingredients. Issue 3 (March 2022) - Okafor, Jane N.C.; Jideani, Victoria A.; Meyer, Mervin; Le Roes-Hill, Marilize
Abstract: The utilization of nutraceuticals on a global scale has significantly increased over the past few years due to their reported health benefits and consumer's reluctance to consume synthetic drugs. This paper provides information regarding new and potential value added uses of biologically active compounds in Bambara groundnut (BGN) as ingredients that could be further researched and exploited for various applications. Nutraceutical is a food or part of food that apart from providing basic nutrients, offers medicinal benefits either by prevention and or treatment of an illness. BGN is a legume with rich nutrient profile that is under exploited industrially. It is widely used in African traditional medicine for its various health outcome, but has not been explored scientifically for its numerous nutraceutical potentials. Compared to beans BGN has greater quantity of soluble fiber and also have high dietary fiber. It is rich in polyphenolic compound which include flavonoids subgroups like flavonols, flavanols, anthocyanindins, isoflavones and phenolic acids: both benzoic acid and cinnamic acid derivatives, biologically active polyunsaturated fatty acids, proteins and peptides, antioxidant vitamins and minerals. The rising interest and emphasis in plant-based biologically active components (nutraceuticals) for various health promotion, has positioned this African legume as a potential source of nutraceutical ingredients (bioactive components) that could be exploited for improved nutrition and health. Abstract : Bioactive components; biological activity, medicinal benefit; phytochemicals, ( Vigna subterraenea (L.) Verdc ).